Good morning yoga : a pose-by-pose wake up story - Gates, Mariam (Sounds True, 2016)
Yoga helps children learn how to focus, relax, and both self-monitor and self-soothe. "Good Morning Yoga" instills these four skills and more, enabling children to jumpstart the day with excitement and meet the adventures that come with mindfulness and perspective.